The extended algebra of algorithms with multiconditional elimination - Ovsyak, V; Ovsyak, A (Видавництво Львівської політехніки, 2010)
The existing, intuitive computation models, that is the virtual machines of Turing, Post, Kolmogorov, Schönhage, Aho-Ullman-Hopcroft as well as the algorithms of Markov and Krinitski, and the recursive functions, all lack precise, mathematical formulation. Consequently, an algebra of algorithms is defined using the axiomatic method. The algebra is based on the operations of sequencing, elimination, paralleling and reversing as well as cyclic sequencing, cyclic elimination and cyclic paralleling, all of them performed on the so-called uniterms. A useful extension is offered in terms of multiconditional elimination. An example illustrates the usefulness of the algebra of algorithms. Вказано відомі методи інтуїтивного опису алгоритмів, якими є віртуальні машини Т’юрінга, Поста, Колмогорова, Шонгаґе, Ахо-Ульмана- Хопкрофта, а також алгоритми Маркова і Крініцкого та рекурсивні функції, засобами яких алгоритми описуються не формалізовано. Дефініцію розширеної алгебри алгоритмів подано аксіоматичним методом. Алгебра базується на операціях секвентування, багатозначного елімінування, паралелення і реверсування, а також циклічного секвентування, циклічного еліміну- вання та циклічного паралелення, які виконуються над унітермами. Розширення торкається введення операції багатозначного елімінування. Прикладом проілюстрована ефективність розширеної алгебри алгоритмів.
Keywords: model; operation; algorithm; definition; модель; операція; алгоритм; визначення